Skip to main content

On Modeling Economic Default Time: A Reduced-Form Model Approach


In the aftermath of the global financial crisis, much attention has been paid to investigating the appropriateness of the current practice of default risk modeling in banking, finance and insurance industries. A recent empirical study by Guo et al. (Rev Deriv Res 11(3): 171–204, 2008) shows that the time difference between the economic and recorded default dates has a significant impact on recovery rate estimates. Guo et al. (, 2011) develop a theoretical structural firm asset value model for a firm default process that embeds the distinction of these two default times. In this paper, we assume the market participants cannot observe the firm asset value directly and we develop reduced-form models for characterizing the economic and recorded default times. We derive the probability distributions of these two default times. Numerical experiments with empirical data are given to demonstrate the proposed models. Our approach helps researchers to gain a new perspective for economic and recorded defaults and is more feasible in general practice compared with current method. Our results can also contribute to the understanding of the impacts of various parameters on the economic and recorded default times.

This is a preview of subscription content, access via your institution.

Fig. 1
Fig. 2
Fig. 3
Fig. 4
Fig. 5


  • Baeka, J., Kangb, J., & Park, K. (2004). Corporate governance and firm value: Evidence from the Korean financial crisis. Journal of Financial Economics, 71, 265–313.

    Article  Google Scholar 

  • Black, F., & Scholes, M. (1973). The pricing of options and corporate liabilities. Journal of Political Economy, 81(3), 637–654.

    Article  Google Scholar 

  • Ching, W., Siu, T., Li, L., Li, T., & Li, W. (2009). Modeling default data via an interactive hidden Markov model. Computational Economics, 34(1), 1–19.

    Article  Google Scholar 

  • Duffie, D., & Garleanu, N. (2001). Risk and valuation of collateralized debt obligations. Financial Analysts Journal, 57(1), 41–59.

    Article  Google Scholar 

  • Duffie, D., & Kan, R. (1996). A yield-factor model of interest rates. Mathematical Finance, 6(4), 379–406.

    Article  Google Scholar 

  • Guo, X., Jarrow, R., & Lin, H. (2008). Distressed debt prices and recovery rate estimation. Review of Derivatives Research, 11(3), 171–204.

    Article  Google Scholar 

  • Guo, X., Jarrow, R., & de Larrard, A. (2011). Economic default time and the Arcsine law, working paper, 2011, available at:

  • Ivashina, V., & Scharfstein, D. (2010). Bank lending during the financial crisis of 2008. Journal of Financial Economics, 97, 319–338.

    Article  Google Scholar 

  • Jacobson, T., Linde, J., & Roszbach, K. (2011). Firm default and aggregate fluctuations, Board of Governors of the Federal Reserve System, International Finance Discussion Papers, number 1029, working paper, 2011.

  • Jarrow, R., & Turnbull, S. (1995). Pricing derivatives on financial securities subject to credit risk. Journal of Finance, 50, 53–86.

    Article  Google Scholar 

  • Lando, D. (1998). On Cox processes and credit risky securities. Review of Derivatives Research, 2, 99–120.

    Google Scholar 

  • Madan, D., & Unal, H. (1998). Pricing the risks of default. Review of Derivatives Research, 2(2–3), 121–160.

    Google Scholar 

  • Merton, R. C. (1974). On the pricing of corporate debt: The risk structure of interest rates. Journal of Finance, 29(2), 449–470.

    Google Scholar 

  • Wu, J., & Yang, W. (2013). Valuation of synthetic CDOs with affine jump-diffusion processes involving Levy stable distributions. Mathematical and Computer Modelling, 57, 570–583.

    Article  Google Scholar 

Download references


The authors would like to thank the referees and the editor for their helpful comments and suggestions. This research work was supported by Research Grants Council of Hong Kong under Grant No. 17301214 and HKU CERG Grants and Hung Hing Ying Physical Research Grant.

Author information

Authors and Affiliations


Corresponding author

Correspondence to Wai-Ki Ching.



Appendix 1: Proof of Proposition 2

We note that Eq. (2) follows from Eq. (1) by using

$$\begin{aligned} P(\tau _r =N_{i+1}\mid \mathcal {G_{\infty }})=P(\tau _e \in (N_i, N_{i+1}] \mid \mathcal {G_{\infty }}). \end{aligned}$$

Eq. (3) follows from Eq. (1) by using

$$\begin{aligned} P(\tau _r-\tau _e > t \mid \mathcal {G_{\infty }})=\sum _{i=0}^{\infty } P(\tau _e \in (N_i, N_{i+1}-t] \mid \mathcal {G_{\infty }}). \end{aligned}$$

And Eq. (1) follows by

$$\begin{aligned} \begin{array}{l@{\quad }l@{\quad }l} &{}&{}P(\tau _e \in (N_i, N_i +t] \mid \mathcal {G_{\infty }})\\ &{}&{}\quad =\displaystyle \sum _{n_i=1}^{K-1}P(S_{N_1} \ne K, \ldots , S_{N_{i-1}} \ne K, S_{N_i} =n_i \mid \mathcal {G_{\infty }})\nonumber \\ &{}&{}\quad \quad \times P(\tau _e \in (N_i, N_i +t] \mid S_{N_i} =n_i, \mathcal {G_{\infty }})\\ &{}&{}\quad =\displaystyle \sum _{n_i=1}^{K-1}\sum _{n_{i-1}=1}^{K-1}\ldots \sum _{n_{1}=1}^{K-1}P(S_{N_1} =n_1, \ldots , S_{N_{i-1}} =n_{i-1}, S_{N_i} =n_i \mid \mathcal {G_{\infty }})\\ &{}&{}\quad \quad \times P_X(N_i, N_i +t)_{n_i, K}\exp \left\{ -\int _{N_i+t}^{N_{i+1}} \lambda _K(X_u) du\right\} \\ &{}&{}\quad =\displaystyle \sum _{n_i\!=\!1}^{K-1}\sum _{n_{i-1}\!=\!1}^{K-1}\ldots \sum _{n_{1}=1}^{K\!-\!1}P_X(N_0, N_1)_{S_0, n_1}\ldots P_X(N_{i-1}, N_i)_{n_{i\!-\!1}, n_i} P_X(N_i, N_i \!+\!t)_{n_i, K}\\ &{}&{}\quad \quad \times \exp \left\{ -\int _{N_i+t}^{N_{i+1}} \lambda _K(X_u) du\right\} \\ &{}&{}\quad =\left( \displaystyle \prod _{j=0}^{i-1} P^{**}_X(N_j, N_{j+1})\cdot P^*_X(N_i, N_i +t)\right) _{S_0, K}\exp \left\{ -\int _{N_i+t}^{N_{i+1}} \lambda _K(X_u) du\right\} . \end{array} \end{aligned}$$

Appendix 2.1: Proof of Proposition 3


Eq.s (12) and (13) are obvious and it suffices to show Eq. (11). Now we have

$$\begin{aligned} \begin{array}{l@{\quad }l@{\quad }l} &{}&{}P(\tau _e \in (N_i, N_i+t]\mid \mathcal {G_{\infty }})\\ &{}&{}\quad =\displaystyle \prod _{j=0}^{i-1}\left( m_1\exp \left[ \int _{N_j}^{N_{j+1}} \mu _1(X_u) du\right] +m_2 \exp \left[ \int _{N_j}^{N_{j+1}} \mu _2(X_u) du\right] \right) \\ &{}&{}\quad \quad \displaystyle \times \left( n_1\exp \left[ \int _{N_{i}}^{N_i+t} \mu _1(X_u) du\right] +n_2 \exp \left[ \int _{N_{i}}^{N_i+t} \mu _2(X_u) du\right] \right) \\ &{}&{}\quad \quad \displaystyle \times \exp \left[ \int _{N_{i}+t}^{N_{i+1}} p_1\mu _1(X_u)+p_2\mu _2(X_u)du\right] \\ &{}&{}\quad = \displaystyle \sum _{\mathbf{e} \in \hat{E}_i} \hat{m}(\mathbf{e})\exp \left[ \int _{N_0}^{N_{i+1}} \hat{\mu }(\mathbf{e},u)du\right] . \end{array} \end{aligned}$$


$$\begin{aligned} P(\tau _e \in (N_i, N_i+t]) =\sum _{\mathbf{e} \in \hat{E}_i} \hat{m}(\mathbf{e}) E\left( \exp \left[ \int _{N_0}^{N_{i+1}} \hat{\mu }(\mathbf{e},u)du\right] \right) . \end{aligned}$$

For a fixed \(\mathbf{e} \in \hat{E}_i\), let

$$\begin{aligned} \begin{array}{l@{\quad }l@{\quad }l} R_{i+1}(\mathbf{e})&{}=&{}p_1 \mu _1+p_2\mu _2\\ R_j(\mathbf{e})&{}=&{}\mu _{e_j}, j=0,1,\ldots , i\\ w_{i+1}(\mathbf{e})&{}=&{}0\\ w_i(\mathbf{e})&{}=&{}\beta (N-t; R_{i+1}(\mathbf{e}), w_{i+1}(\mathbf{e}))\\ w_{i-1}(\mathbf{e})&{}=&{}\beta (t; R_{i}(\mathbf{e}), w_{i}(\mathbf{e}))\\ w_j(\mathbf{e})&{}=&{}\beta (N; R_{j+1}(\mathbf{e}), w_{j+1}(\mathbf{e})), j=0, 1, \ldots , i-2\\ v_{i+1}(\mathbf{e})&{}=&{}\exp [\alpha (N-t; R_{i+1}(\mathbf{e}), w_{i+1}(\mathbf{e}))]\\ v_{i}(\mathbf{e})&{}=&{}\exp [\alpha (t; R_{i}(\mathbf{e}), w_{i}(\mathbf{e}))]\\ v_{j}(\mathbf{e})&{}=&{}\exp [\alpha (N; R_{j}(\mathbf{e}), w_{j}(\mathbf{e}))], j=0, 1, \ldots , i-1.\\ \end{array} \end{aligned}$$

Then we can rewrite \(\hat{\mu }(\mathbf{e}, s)\) as

$$\begin{aligned} \hat{\mu }(\mathbf{e}, s)&= 1_{\{s \in [N_i+t, N_{i+1})\}}(R_{i+1}(\mathbf{e}) X_s)+1_{\{s \in [N_i, N_i+t)\}}(R_{i}(\mathbf{e})X_s) \\&+ \sum _{j=0}^{i-1} 1_{\{s \in [N_j, N_{j+1})\}}(R_j(\mathbf{e}) X_s). \end{aligned}$$

Using the iterated expectation and Eq. (10) we obtain

$$\begin{aligned} \begin{array}{lll} &{} &{}E\left( \exp [\int _{N_0}^{N_{i+1}} \hat{\mu }(\mathbf{e},u)du]\right) \\ &{}&{}\quad =E\left( \exp [\int _{N_0}^{N_{i}+t} \hat{\mu }(\mathbf{e},u)du]E(\exp [\int _{N_{i}+t}^{N_{i+1}} R_{i+1}(\mathbf{e})X_u du] \mid \mathcal {G}_{N_i+t})\right) \\ &{}&{}\quad =v_{i+1}(\mathbf{e})E\left( \exp [\int _{N_0}^{N_{i}+t} \hat{\mu }(\mathbf{e},u)du] \exp [w_i(\mathbf{e}) X_{N_i+t}]\right) \\ &{}&{}\quad =v_{i+1}(\mathbf{e}) E\left( \exp [\int _{N_0}^{N_{i}} \hat{\mu }(\mathbf{e},u)du]E(\exp [\int _{N_{i}}^{N_{i}+t} R_{i}(\mathbf{e})X_u du+w_i(\mathbf{e}) X_{N_i+t}] \mid \mathcal {G}_{N_i})\right) \\ &{}&{}\quad =v_{i+1}(\mathbf{e})v_{i}(e) E\left( \exp [\int _{N_0}^{N_{i}} \hat{\mu }(\mathbf{e},u)du] \exp [w_{i-1}(\mathbf{e})X_{N_i}]\right) \\ &{}&{}\quad \!\!=v_{i\!\!+\!\!1}(\mathbf{e}) v_{i}(\mathbf{e}) E\left( \exp [\int _{N_0}^{N_{i\!\!-\!\!1}} \hat{\mu }(\mathbf{e},u)du]E(\exp [\int _{N_{i-1}}^{N_{i}} R_{i-1}(\mathbf{e})X_u du\!\!+\!\!w_{i-1}(\mathbf{e})\right. \\ &{}&{}\quad \left. X_{N_i}] \mid \mathcal {G}_{N_{i-1}})\right) \\ &{}&{}\quad =v_{i+1}(\mathbf{e}) v_{i}(\mathbf{e}) v_{i-1}(\mathbf{e}) E\left( \exp [\int _{N_0}^{N_{i-1}} \hat{\mu }(\mathbf{e},u)du] \exp [w_{i-2}(\mathbf{e})X_{N_{i-1}}]\right) \\ &{}&{}\quad =\left( \prod _{j=0}^{i+1} v_j(\mathbf{e})\right) \exp [\beta (N; R_0(\mathbf{e}), w_0(\mathbf{e})) X_0] \ \mathrm{(by \ iteration)} \end{array} \end{aligned}$$

Hence Eq. (11) follows. \(\square \)

Appendix 2.2: Proof of Proposition 4


We let

$$\begin{aligned} H_i(X_0, t):=P(\tau _e \in (N_i, N_i+t]) \end{aligned}$$

then by the proof of Proposition 3, for \(i\ge 1\),

$$\begin{aligned} P(\tau _e \in (N_i,N_i+t]\mid \mathcal {F}_{N_1})&= \left( m_1\exp \left[ \int _{N_0}^{N_1}\mu _1(X_u) du\right] \right. \nonumber \\&\left. +\,m_2\exp \left[ \int _{N_0}^{N_1}\mu _2(X_u) du\right] \right) H_{i-1}(X_{N_1}, t)\nonumber \\ H_i(X_0, t)&= E\left[ \left( m_1\exp \left[ \int _{N_0}^{N_1}\mu _1(X_u) du\right] \right. \right. \nonumber \\&\left. \left. +\,m_2\exp \left[ \int _{N_0}^{N_1}\mu _2(X_u) du\right] \right) H_{i-1}(X_{N_1}, t)\right] \end{aligned}$$

By Proposition 3, we obtain that

$$\begin{aligned} H_0(x, t)=a_{0,1}\exp (b_{0,1}x)+a_{0,2}\exp (b_{0,2}x). \end{aligned}$$

Combining Eqs. (16) and (10), Proposition 4 follows. \(\square \)

Appendix 3

Let \(\delta =18\) days, \(t_i=\delta i, i=0, 1, \ldots , 10\). Let \(N_i\) denote the number of firms whose time difference of economic and recorded default date is inside the interval \((t_{i-1}, t_i]\). Then the log-likelihood function is given by

$$\begin{aligned} \begin{array}{l@{\quad }l@{\quad }l} \displaystyle \mathcal {L}(\lambda _1,\lambda _2) &{}=&{} \displaystyle \sum _{i=1}^{10} N_i \left( \ln \left[ (e^{-\lambda _2 t_{i-1}}-e^{-\lambda _2 t_{i}})-e^{-(\lambda _1+\lambda _2)N}(e^{\lambda _1 t_{i-1}}-e^{\lambda _1 t_{i}})\right] \right. \\ &{}&{} \displaystyle \left. -\ln \left[ 1-e^{-(\lambda _1+\lambda _2)N} \right] \right) \end{array} \end{aligned}$$

By setting

$$\begin{aligned} \left\{ \begin{array}{l@{\quad }l@{\quad }l} \displaystyle \frac{\partial \mathcal {L}(\lambda _1,\lambda _2)}{\partial \lambda _1}=0\\ \displaystyle \frac{\partial \mathcal {L}(\lambda _1,\lambda _2)}{\partial \lambda _2}=0, \end{array} \right. \end{aligned}$$

we have two nonlinear equations for \(\lambda _1\) and \(\lambda _2\). Solving these equations numerically yields \(\lambda _1=0.3631\) and \(\lambda _2=0.0238\).

Rights and permissions

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Gu, JW., Jiang, B., Ching, WK. et al. On Modeling Economic Default Time: A Reduced-Form Model Approach. Comput Econ 47, 157–177 (2016).

Download citation

  • Accepted:

  • Published:

  • Issue Date:

  • DOI:


  • Economic default time
  • Reduced-form model
  • Affine jump diffusion model